The lure of land: peasant politics, frontier colonization and the cunning state in Sri Lanka - Kelegama, T; Korf, B (Cambridge University Press, 2023)
This paper studies the contradictions of peasant politics in Sri Lanka's dry zone frontier in a highly militarized colonization scheme ('System L' of the Mahaweli Development Programme in Weli Oya in northern Sri Lanka). Through a detailed ethnographic study of the life histories of settlers who came in two waves to this scheme (1980s and post-2009), we show the workings of what we call the 'lure of land': first, as the (al)lure that attracts landless families to live out the mythical dream of becoming a paddy farmer; second, this lure of land is intimately tied to a nationalist territorial aspiration that transforms the settler into a patriotic colonizer of the land: due to its strategic location in the frontier zone between Sinhalese and Tamil inhabited territories, settlers became 'home guards' who live on and protect the frontier. But the lure of land is not without contradictions: Life in the frontier is dangerous (for the early settlers) and economically precarious (for the early and late settlers), because the state is unable to deliver the promise of land and water. Government officials deploy various tactics of repeatedly deferred promises and subtle threats to discourage settlers to abandon the colonization scheme despite the settlers' precarious life conditions, disappointments, and frustrations. A 'cunning state' thereby betrays its own 'frontiersmen', while safeguarding its nationalist territorial agenda.